Dialogues in space-time: At the crossroads between Arts Education and Cultural Citizenship - Matos Pereira, Teresa Isabel; Pereira Antunes, Sandra; Gaudêncio Matos, Joana; Correia Ferreira, Joana (European Public & Social Innovation Review, 2024)
Introduction: This article focuses on a teaching-learning process developed within the context of initial training for teachers and educators, involving practices in the visual arts. Methodology: A qualitative study was conducted, considering the generation of data from artistic-pedagogical practices and its respective content analysis. Results: Creative processes and resulting materials were analyzed, including photographic series, mind maps and visual essays, as well as the students' critical reflections recorded in their learning portfolios. Discussions: The simultaneous visual and discursive dimensions of the produced materials, as well as the gathered reflections, allowed us access to a set of meanings attributed to the carried-out processes, which encompassed areas such as technical knowledge, creativity, communication, interpersonal relationships and a sense of professionalship. Conclusions: The articulation of the aforementioned domains, in the context of integrated arts education into teacher training, allowed us to observe the impasses, potentialities and, above all, the urgency for education professionals to assume a lively stance in face of a context of uncertainty and rapid social and cultural change. This requires a critical view of realities and truths, an ability to co-create healthy learning environments that promote inclusion and equity, freedom of choice, and creativity in its broadest sense.